(untitled) (Research, Society and Development, 2022)
Self-mutilation is a non-suicidal and intentional self-inflicted aggression that is not socially accepted. The constant rise of self-injury among the youth points that this practice is not caused only by individual factors, emerging the need to investigate if there are factors that provoke collective suffering and induce self-mutilation. The objective was to explore the influence of factors from contemporaneity on the occurrence of self-mutilation in adolescents. The method was an integrative literature review with searches in four databases. From the results, eight studies were included. It is possible to understand that the contemporaneity’s way of functioning is covered by an uneasiness that acts over the individuals. In adolescence, loneliness and helplessness interfere with the symbolization and elaboration of emotional pain. Therefore, self-injury becomes an expression of suffering and uneasiness. Simultaneously, suffering can be addressed on social networks, reinforcing the practice’s contagious effect.